Pertumbuhan dan Hasil Produksi Jamur Tiram Putih (Pleorotus ostreatus) pada Variasi Media Tumbuh yang Diperkaya Limbah Organik: Growth and Yield of White Oyster Mushroom (Pleurotus ostreatus) on Various Organic Waste-Enriched Growth Media - Ramdhoani; Luh Putu Yuni Widyastuti; Bahasa Indonesia; Ni Putu Eka Pratiwi (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2025)
White oyster mushrooms (Pleurotus ostreatus) have high economic value due to their nutritional content and the increasing market demand. However, optimizing an effective and environmentally friendly growing medium remains a challenge. This study aims to determine the effect of variations in growing media enriched with organic waste from coffee husks, sugarcane bagasse, and cocoa husks on the growth and yield of oyster mushrooms. The research was conducted from May to September 2023 at Bee Jamur, Peguyangan Village, Bali. The method used was a split-plot design. The first factor, as the main plot, consisted of three types of organic waste: coffee husks (L1), cocoa husks (L2), and sugarcane bagasse (L3). The second factor, as the subplot, comprised eight organic waste compositions: K1 = 100% sawdust (control); K2 = 15% organic waste (LO); K3 = 25% LO; K4 = 35% LO; K5 = 45% LO; K6 = 55% LO; K7 = 65% LO; K8 = 75% LO. The results showed that using organic waste as an additive in the growing medium increased mycelium growth speed, wet weight, and the physical characteristics of the oyster mushrooms compared to the control. The medium with the addition of coffee husks yielded the best results in terms of growth and mushroom production. Furthermore, organoleptic tests showed that mushrooms grown using sugarcane bagasse media were the most preferred in aroma, texture, and taste. Keywords: baglog, mushroom, coffee husks, cocoa husks, sugarcane bagasse